Paracrine/autocrine control of spermatogenesis by gonadotropin-inhibitory hormone - Fallah, Hamideh P.; Tovo-Neto, Aldo [UNESP]; Yeung, Edward C.; Nóbrega, Rafael H. [UNESP]; Habibi, Hamid R. (Elsevier, 2019)
Control of testicular development is multifactorial and involves a number of hypothalamic, hypophyseal and peripheral hormones. Here, we investigated direct action of zebrafish gonadotropin-inhibitory hormone (zGnih) which is expressed in the testis, on spermatogenesis in zebrafish, in vitro. Treatment with zGnih at the lower doses (10 and 100 nM) inhibited gonadotropin-induced spermatids/spermatozoa (SPD/SPZ) production. However, at the highest dose (1000 nM), zGnih increased basal number of SPD/SPZ and showed paradoxical effect. The effects of zGnih on testosterone and SPD/SPZ production was blocked in the presence of androgen receptor antagonist, flutamide (FLU). A number of transcripts were also measured to better understand zGnih mechanisms of action on zebrafish spermatogenesis. Our results provide strong support for the hypothesis that locally produced zGnih is a component of the complex multifactorial system that regulates testicular development and function in adult zebrafish, in part, by changes in testicular steroidogenesis and regulation of gonadotropin-induced response.
Keywords: Flutamide (FLU); Gonadotropin-inhibitory hormone (Gnih); Human chorionic gonadotropin (hCG); Spermatids (SPD); Spermatozoa (SPZ); Testosterone; Zebrafish gnih (zGnih)